2010
DOI: 10.1371/journal.pone.0010132
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenase-3 Contributes to Anaerobic Acid Resistance of Escherichia coli

Abstract: BackgroundHydrogen production by fermenting bacteria such as Escherichia coli offers a potential source of hydrogen biofuel. Because H2 production involves consumption of 2H+, hydrogenase expression is likely to involve pH response and regulation. Hydrogenase consumption of protons in E. coli has been implicated in acid resistance, the ability to survive exposure to acid levels (pH 2–2.5) that are three pH units lower than the pH limit of growth (pH 5–6). Enhanced survival in acid enables a larger infective in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 46 publications
6
69
1
5
Order By: Relevance
“…Thus, it is unlikely that oxalate is utilized as a metabolite in a proton-consuming reaction, like glutamate or arginine in AR2 or AR3. Formate, one of the products of the YfdWU-catalyzed reaction, mediates acid resistance when included in the challenge medium (70). Noguchi et al showed previously that knockouts of hydE (Hyd-3), a component in the formate hydrogen lyase (FHL) complex, grown to stationary phase in rich medium (LBK) at pH 5.0 and then challenged anaerobically at pH 2 and 2.5 in rich medium (LBK) showed reduced acid resistance compared to the other Hyd mutants and wild-type E. coli (W3110) (70).…”
Section: ϫ5mentioning
confidence: 99%
“…Thus, it is unlikely that oxalate is utilized as a metabolite in a proton-consuming reaction, like glutamate or arginine in AR2 or AR3. Formate, one of the products of the YfdWU-catalyzed reaction, mediates acid resistance when included in the challenge medium (70). Noguchi et al showed previously that knockouts of hydE (Hyd-3), a component in the formate hydrogen lyase (FHL) complex, grown to stationary phase in rich medium (LBK) at pH 5.0 and then challenged anaerobically at pH 2 and 2.5 in rich medium (LBK) showed reduced acid resistance compared to the other Hyd mutants and wild-type E. coli (W3110) (70).…”
Section: ϫ5mentioning
confidence: 99%
“…Согласно исследованиям [18], основная роль Hyd-3 гидрогеназы связана с наработкой молекулярного водорода (Н 2 ) при окислении формата Fdh-H дегидрогеназой. Экспрессия оперона hyc, кодирующего структуру Hyd-3, оптимальна в кислой области значений рН и в отсутствие глюкозы в среде [18,19].…”
Section: реконструкция молекулярно-генетического механизма формированunclassified
“…Экспрессия оперона hyc, кодирующего структуру Hyd-3, оптимальна в кислой области значений рН и в отсутствие глюкозы в среде [18,19]. Показано также, что основным ферментом, потребляющим Н 2 в анаэробных условиях, является Hyd-2 гидрогеназа [18].…”
Section: реконструкция молекулярно-генетического механизма формированunclassified
See 2 more Smart Citations